The issues of safety and pharmacoeconomics in the management of chronic pain in the back and limbs - Vladimir Anatol'evich Parfenov; O N Gerasimova; Vladimir Anatolyevich Parfenov; O N Gerasimova (Современная ревматология, 2011)
Nonsteroidal anti-inflammatory drugs (NSAIDs), the long-term administration of which is associated with a risk for complications, gastrointestinal tract (GIT) ones in particular, are extensively used to treat chronic pain in the back and limbs. The paper reviews the data available in the literature on adverse reactions occurring with the use of NSAIDs, discusses the issues of pharmacoeconomics in the administration of various NSAIDs. The use of the selective cyclooxygenase-2 inhibitor meloxicam (Movalis) is noted to cause fewer GIT adverse reactions than that of standard NSAIDs, the cost of treatment for GIT complications reduces.